Plant cover, floristic diversity and similarity of wet meadows grazed by free-ranging cattle in Axios Delta, Greece - Papaporfyriou P.; Chouvardas D.; Tsiripidis I.; Abraham E.M. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Wet meadows constitute valuable habitats for the wild flora and fauna and important resource for extensive animal husbandry, despite their limited extent. The objective of this research was to study the plant cover, floristic diversity and similarity of wet meadows under the effect of grazing. The study area was located in Axios Delta, northern Greece which has been grazed by free-ranging cattle throughout the year. Five subareas were selected in a distance of 500 and 1400 m away from the cattle shed (indicating differences in grazing intensity) namely; ‘riparian-1400m’, ‘central-500m’, ‘central-1400m’, ‘channel-500m’, ‘channel-1400m’. The riparian area received higher amount of freshwater compared to the channel and central areas. Measurements of cover and vegetation composition were performed in eight plots in each of the subareas. Differences between the five subareas were tested by means of one way ANOVA and LSD test. The subarea riparian-1400m presented the highest rates of plant cover and floristic diversity, mainly due to the high soil moisture and low grazing intensity. Plant cover tended to be increased away from the shed, probably because of the decrease of grazing intensity. The similarity index was higher in the drier central subareas with higher soil salt content owing to the halophytes dominance in them.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)